Performance of Public Service Apparatus at the Population and Civil Registration Office of Ogan Ilir Regency - Masayu Adiah; Nyms Nadira Sayba (Penerbit Jurnal Indonesia, 2021)
The Department of Population and Civil Registration is the implementing element of government affairs in the field of civil registration, in which there is management in the process of carrying out a job with a series of sequential, continuous actions that are carried out to achieve something that has been determined. In accordance with the mission of Ogan Ilir Regency, among others, namely realizing and improving the performance of local government officials who can serve the community excellently, making good governance (Good Governance), honest, free from corruption, collusion and nepotism practices. The author is interested in conducting research at the Office of Population and Civil Registration of Ogan Ilir Regency with the title Public Service Apparatus Performance at the Population and Civil Registration Office of Ogan Ilir Regency. The problem of this research is limited to matters relating to the role of the service apparatus in providing services to the community. The research focuses on the performance of the service apparatus in the Population and Civil Registration Office of Ogan Ilir Regency. The purpose of this study is to analyze and describe the performance of public service apparatus in the Department of Population and Civil Registration of Ogan Ilir Regency, supporting and inhibiting factors in the public service of the apparatus at the Department of Population and Civil Registration of Ogan Ilir Regency. This study uses a qualitative approach. According to Lexy J. Moleong (2013) qualitative research is research that produces analytical procedures that do not use other qualification analysis procedures. In determining the operational variables of qualitative research, initially the problems studied were still general. Research will become clearer when researchers are in the field. Based on the results of the study, it was concluded that the public service performance of the apparatus at the Population and Civil Registration Office of Ogan Ilir Regency was overall good. However, there are still weaknesses in terms of timeliness of service, ease of service and accuracy in service. The suggestion submitted is that the Population and Civil Registration Office of Ogan Ilir Regency should coordinate with related parties. Thus, service delays can be overcome.